Determination of esports players' levels of life engagement and future expectations in terms of various variables in Turkey - Cuma Ece; Semra Çetin; Murat Şen; Mehmet Koç (ROL Spor Bilimleri Dergisi)
If we were to make a scientific definition, electronic sports; “The field of sports activities, in which people develop and train their mental or physical abilities using information and communication technologies, is one of the biggest types of entertainment. The aim of this study is to reveal the relationship between esports players' life engagement and their expectations from the future. A total of 243 people, 145 men and 79 women, aged 18.155 ± 1.05 years, residing in the Marmara region of Turkey, participated in the research, which was carried out as a descriptive and relational survey. In the research, the Life Engagement Scale and the Adolescent Future Expectations Scale were used. No difference was found between the overall score averages of the scale of life engagement and future expectation of esports players and the variable of father's education and income levels (p> 0.05). It has been determined that esports players whose mother's education level is secondary school have higher religion and society levels (p< 0.05). According to the gender variable, it was determined that the level of life engagement and future expectation of esports players differed between the sub-dimensions of the scale (p< 0.05). As a result of the research, a positive correlation was found between the esports players' life engagement and the mean score of the scale of future expectation and the sub-dimensions of the scale of future expectation (p< 0.05). It is recommended that similar studies be conducted in larger groups and in different regions.